Pengaruh Store Atmosphere, Faktor Emosional Pelanggan, Dan Nilai Pelanggan Terhadap Keputusan Pembelian (Studi Pada Trijata Koffie) - Rahimah, Azka Rizky; Asiyah, Siti; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of store atmosphere, customer emotional factors, and customer value on purchasing decisions at Trijata Koffie. The location of this research was carried out in Malang City. This research is quantitative research. The population used in this research is consumers who have made a purchase at Trijata Koffie at least once, with a sample of 70 respondents. Respondent characteristics are consumers who have made a purchase at least once and are aged 17-35 years. This research uses non-probability sampling techniques with purposive sampling. The data collection technique uses an online questionnaire. The analysis tool uses multiple linear regression analysis. The results of this research show that store atmosphere, customer emotional factors, and customer value have a simultaneous influence on purchasing decision variables. Store atmosphere has a positive and significant effect on purchasing decisions. Customer emotional factors have a positive and significant influence on purchasing decisions. Customer value has a positive and significant effect on purchasing decisions. Keywords: Store Atmosphere, Customer Emotional Factors, Customer Value, and Purchasing Decisions